Literature Review: The Influence of Primary School Level Health Education on Knowledge of Clean and Healthy Living Behaviors - Muharani, Anisa; Fahlevi, M Reza; Mawaddah, Qisti; Priyatna, Sekar Harum; Munika, Tia; Sintia, Tri Rahma; Zakaria, Nisrina (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Introduction: Knowledge about life and cleanliness at school is very important to know and can support students' behavior to live a better life. Objective: Writing this Literature Review aims to determine the relationship between knowledge and clean and healthy living behavior in elementary school children. Method: This research used the Literature Review method by taking data sources using an electronic database, namely Google Scholar with scientific articles published in the last 8 years. Results: There are 7 articles that have a relationship and influence with Knowledge of Clean and Healthy Living Behavior. Conclusion: From The results of the analysis of 7 Literature Review journals showed that some students still lacked knowledge to implement a clean and healthy lifestyle. Therefore, it is hoped that efforts will be made to provide education to elementary school students on an ongoing basis.